2010
DOI: 10.1094/phyto-100-5-0424
|View full text |Cite
|
Sign up to set email alerts
|

Early Events Prior to Visual Symptoms in the Apoplectic Form of Grapevine Esca Disease

Abstract: Plant infection by pathogens generates various forms of symptoms. Most of them have been described as soon as they become visible, whereas preceding, discrete signs during incubation are poorly or not understood. In Vitis vinifera, esca-related pathogenic fungi inhabit living trunk wood and induce the so-called apoplexy, a sudden wilting of leaves within a few days. To further understand the apoplexy expression, the period preceding symptom appearance was investigated by following physiological and molecular m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
54
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 54 publications
9
54
0
Order By: Relevance
“…In agreement with our observation, most studies have also reported the induction of an antioxidant system (through catalytic activity, proteins expression or transcripts accumulation) on grapevine organs affected by trunk diseases (leaves [40,47,48,49]; green stem [35]; wood [36]). By scavenging the AOS formations, the plant’s antioxidant system protects against toxic oxygen intermediates [50].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In agreement with our observation, most studies have also reported the induction of an antioxidant system (through catalytic activity, proteins expression or transcripts accumulation) on grapevine organs affected by trunk diseases (leaves [40,47,48,49]; green stem [35]; wood [36]). By scavenging the AOS formations, the plant’s antioxidant system protects against toxic oxygen intermediates [50].…”
Section: Resultssupporting
confidence: 91%
“…Only one protein involved in responses to oxidative stresses, a thioredoxin H-type (s3015), was over-regulated in response to wounding (C2F) or fungal infection (DsF and NpF), while the abundance of a superoxide dismutase (SOD, s5018) decreased in the stem infected by Ds. Reduced expression of SOD was also reported in other organs of the vine affected by trunk diseases, green stems [35], leaves [48,49]) and trunk [36]. Similarly to the G stage, PRP-10 (s5016) and HSPs (s3014, s2123) abundance increased in the stem in response to fungal infection, particularly with Ds (Table 2).…”
Section: Resultsmentioning
confidence: 55%
“…It has been suggested that the biphasic gene accumulation may allow the plant to adapt to a specific attack and modulate the defence response; the biphasic shape results of the consecutive expression of two types of genes: a first type quickly expressed after elicitation with a rapid degrading mRNA, followed by a second slowly expressed gene type (Wiese et al 1994). Particularly in what concerns increased expression of PAL and STSY after infection, the results here obtained in cell cultures agree with results obtained in vivo in escaaffected grapevines -in which the presence of P. chlamydospora was confirmed (Letousey et al 2010).…”
Section: Discussionsupporting
confidence: 86%
“…This may explain the high number of aquaporin encoding genes found in our fifty most down-regulated genes. On the other hand, down-regulation of genes encoding aquaporins in soybean infected by soybean rust is similar to what has been reported in esca-infected grapevine where some aquaporin encoding genes were repressed at late stages of the infection (Letousey et al, 2010). Deep sequencing allowed the analysis of expression of genes encoding proteins associated with salicylic acid (SA) biosynthesis, which is involved in defense.…”
Section: Soybean Gene Expression Profilesupporting
confidence: 67%